Infrastructure Financing: Trends, Challenges, and Future Directions - Mustapha, Isiaka Kolawole (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: Infrastructure financing is critical for global development, yet it remains constrained by challenges such as funding deficits, regulatory complexities, and the need for sustainable and technologically driven solutions. The review aims to explore trends, challenges, and future directions in infrastructure financing, providing a comprehensive synthesis of current knowledge and identifying gaps for further research. Methodology: This systematic literature review (SLR) adopts the PSALSAR methodology—Protocol development, Search, Appraisal, Literature synthesis, Analysis, and Report writing—to analyse 72 peer-reviewed studies published between 2014 and 2024. Findings: A structured search across academic databases yielded relevant literature, which was rigorously appraised against predefined inclusion criteria. The thematic analysis revealed key trends, including the growing reliance on public-private partnerships (PPPs), the integration of digital technologies like fintech and blockchain, and the emergence of green financing instruments such as green bonds and Islamic bonds. Key challenges identified include inadequate risk-sharing mechanisms, regulatory inconsistencies, and socio-political uncertainties. Also, 75% of the studies on infrastructure financing are dominated by articles from developing countries. This SLR recognizes knowledge gaps in relation to the context, theory and content for future research. Originality/value: This paper is original